1984
DOI: 10.1152/jappl.1984.56.6.1659
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of tidal volume, lung volume, and flow measurements by inductance vest in COPD patients

Abstract: We analyzed the accuracy of the inductance vest in measuring several ventilatory parameters in five patients with chronic obstructive pulmonary disease (COPD). We assessed tidal volume (VT) accuracy at different respiratory frequencies in different lying body positions with different thoracic and abdominal contributions to breathing and the accuracy over a 4-h time span. Mean percent error was calculated without regard to direction of error. The mean error of vest VT estimation was 7.6% for all body positions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…HUDGEL et al [17] demonstrated a similar agreement of flow traces from PTG and calibrated inductance vest in chronic obstructive pulmonary disease (COPD) patients. MAXWELL et al [18] used calibrated RIP to estimate lung volume changes during histamine-induced bronchoconstriction in recurrently wheezy infants.…”
Section: Discussionmentioning
confidence: 76%
“…HUDGEL et al [17] demonstrated a similar agreement of flow traces from PTG and calibrated inductance vest in chronic obstructive pulmonary disease (COPD) patients. MAXWELL et al [18] used calibrated RIP to estimate lung volume changes during histamine-induced bronchoconstriction in recurrently wheezy infants.…”
Section: Discussionmentioning
confidence: 76%
“…In clinical pulmonary function tests, the specific manifestations of COPD p include decreased FEV1/FVC levels [28], as well as reduced expressions of MMEF and other ventilation indicators [29]. Diminished levels of basic and superimposed lung volume indicators, such as ERV, inspiratory reserve volume (IRV), and FRC, are also indicative of COPD [30]. Unlike clinical data, the pulmonary data collected from animal models are affected by existing instruments, and the indicators of different instruments may vary.…”
Section: Effect Of Incremental Smoke Exposure On Lung Function and Stmentioning
confidence: 99%
“…Lennox and coworkers (41) found that drift of an inductive plethysmography signal was only 22% of the drift arising from changes in temperature within a body plethysmograph. Other investigators (42)(43)(44) have also reported that drift of inductive plethysmography is small over short periods. Artifactual changes in volume related to drift were further minimized by relating changes in end-expiratory lung volume to a reference point within that same cycle of Cheyne-Stokes respiration, namely the lung volume during the preceding apnea.…”
Section: Methodologic Considerationsmentioning
confidence: 90%